PELAKSANAAN JAM PENGGANTI MATA PELAJARAN SENI BUDAYA MATERI AJAR PENDALAMAN TEKNIK BERNYANYI DI KELAS IX.4 SMP NEGERI 40 PADANG - Cahya Ain Ramadhani; Syeilendra (Universitas Negeri Padang, 2026)
This study aims to describe the implementation of substitute class hours in Cultural Arts subjects focusing on singing technique enrichment in Grade IX.4 at SMP Negeri 40 Padang. The research employed a qualitative descriptive approach using observation, interviews, and documentation as data collection techniques. The participants included a Cultural Arts teacher and 32 Grade IX.4 students. The findings indicate that substitute class hours serve as an effective means to strengthen students’ understanding of vocal techniques, particularly breathing, articulation, intonation, and musical expression. The use of active learning strategies and formative assessment contributed to increased student engagement, motivation, and vocal performance. Despite challenges such as limited time, student fatigue, and minimal learning media, substitute classes positively supported learning achievement. The study concludes that substitute class hours can function as an effective alternative to ensure continuity in Cultural Arts learning.